Предмет: Алгебра, автор: ignatova121209

Будь ласка СРОЧНО !!!!!!!!!!!!!!!!!!!!!!!!!!!!!

Приложения:

Ответы

Автор ответа: Petia228
1

a)\\ x^2 + (a+b)x + ab = (a + x)(x + b)\\x^2 + (a+b)x + ab = ax + ab + x^2 + bx\\x^2 + (a+b)x + ab = x^2 + (ax + bx) + ab\\x^2 + (a+b)x + ab = x^2 + (a + b)x + ab

b) \\x^2 - (a+b)x + ab = (x-a)(x-b)\\x^2 - (a+b)x + ab = x^2 -bx - ax +ab\\x^2 - (a + b)x + ab = x^2 - (ax+bx)+ab\\x^2 - (a+b)x + ab = x^2 - (a+b)x+ab

Похожие вопросы
Предмет: Математика, автор: ilovekimsunoo2003